Leverage Moderates the Effect of Capital Intensity on Accounting Conservatism in Metal Sub Sector Manufacturing Companies Listed on the IDX In 2018-2022 - Monica; Juita Sukraini; Nidia Anggreni Das (Future Science, 2024)
This study aims to determine the Effect of Capital Intensity (X) on Accounting Conservatism (Y) with Leverage (Z) as a moderating variable in Metal Sub-Sector Manufacturing Companies listed on the Indonesia Stock Exchange in 2018-2022. The results of this study indicate that Capital Intensity has no effect on Accounting Conservatism. This result is evidenced by the calculated t of 1.289 <t table value of 2.005 and a significant value of 0.203> 0.05. After that Leverage strengthens the relationship between Capital Intensity and Accounting Conservatism. This result is evidenced by the results of the Moderate Regression Analysis (MRA) test seen from the determination coefficient (R2) value in the regression equation structure 1, which is 3% <the determination coefficient (R2) value in the regression equation structure 2, which is 4.1%. This can also be seen from the slope value in the regression equation structure 2, where the regression coefficient X * Z is positive, which is 1%.